Chemotherapy-Induced Nausea and Vomiting (CINV) Based on Blood Types among Cancer Patients in Yogyakarta, Indonesia - Dwi Kartika Rukmi; Muhamat Nofiyanto (Nurse Media Journal of Nursing, 2023)
Background: Studies related to blood type in cancer patients have been conducted extensively, but they are inclined to cancer incidence or survival rate. Meanwhile, there is limited research on Chemotherapy-Induced Nausea and Vomiting (CINV), the most disturbing side effect of chemotherapy, in relation to blood type.Purpose: This study aimed to compare CINV frequency in cancer patients by blood groups in Yogyakarta, Indonesia.Methods: A descriptive comparative study with a cross-sectional approach was conducted purposively on 70 chemotherapy patients in two hospitals in Yogyakarta. Patients with anticipatory CINV and brain cancer (primary or metastases) were excluded. The data were collected between July and November 2020 using a sheet for patient characteristics and a filled-in diary from the first to the seventh day post-chemotherapy to collect CINV data. The descriptive statistics and Kruskal Wallis test were used to analyze the data.Results: Of 70 total samples, most of them were breast cancer (71.4%) and were in stage IV (50%). They received chemotherapy alone as their primary therapy (94.3%) and received moderate to high emetogenic agents (31.4% and 35.7%). Samples mostly had A blood type (34.3%) and had undergone chemotherapy for 3-18 months (min-max). As many as 64.6% of patients experienced CINV with a delayed type and experienced moderate severity (52.9%). The bivariate test showed no difference in CINV frequencies based on blood groups in general (p=0.068). However, based on the CINV onset, there was a significant difference in CINV frequencies in the A blood group against other blood groups (p=0.020) on the fourth post-chemotherapy day.Conclusions:Unless the fourth-day post-chemotherapy, the frequency of CINV based on blood groups showed no difference. Since CINV incidence is still high, the provision of both pharmacological and non-pharmacological therapy to treat CINV has to be given to patients after chemotherapy. Blood group factors can be considered for more extensive management, especially in delayed CINV cases.